Repository Evaluation of Software Reuse: An Empirical Study - BANKER, R. D. (Institutional Knowledge at Singapore Management University, 1993)
The use and benefits of repository evaluation of software reuse are illustrated through an analysis of the evolving repositories of two large firms that recently implemented integrated CASE development tools. The analysis shows that these tools have supported high levels of software reuse, but it also suggests that there remains considerable unexploited reuse potential. The findings indicate that organizational changes will be required before the full potential of the new technology can be realized.